Fibrinolytic activities of a medicinal mushroom: Lignosus rhinocerotis (Cooke) ryvarden / Kho Tieng Tieng - Kho, Tieng Tieng (2014)
Ganoderma lucidum, Cordyceps militaris, Lignosus rhinocerotis, Pleurotus giganteus, Pleurotus floridanus and Auricularia polytricha were screened for fibrinolytic activity using fibrin plate assay. Fibrinolytic activity was identified in the fruiting bodies of the medicinal mushrooms L. rhinocerotis and A. polytricha. However, the present study emphasised on the evaluation of the fibrinolytic activity from L. rhinocerotis and its partially purified enzyme only. Fibrin plate assay showed 1.2 cm of lytic zone by the crude extracts of L. rhinocerotis which doubled in lytic zone size after overnight incubation, which demonstrated the stability of the fibrinolytic enzyme. The extract was initially dialysed using 12 kDa cellulose membrane and the solution was freeze-dried and stored under -20oC prior to use. Aqueous two phase system (ATPS), a single-step purification method was applied to partition and concentrate the protein. In addition, pre-chilled acetone was used to remove contaminants and precipitate the protein through centrifugation at 13,000 – 15,000 g. A PEG 8000/ phosphate system comprising of 4.0 g of 50% of polyethylene-glycol (PEG), 2.9 g of 40% of phosphate solution and pH 7.0 resulted in the concentration of fibrinolytic enzyme in the top phase, with specific activity 151.61 U / mg (2.67 fold). The molecular mass of the partially purified enzyme was identified through SDS-PAGE and estimated to be between 55 kDa and 60 kDa. Native PAGE was carried out for gel excision in which band of interested (partially purified enzyme) was excised and purified from polyacrylamide gel using elution buffer. Then, the eluted sample was tested on fibrin plate and resulting in the confirmation of the fibrinolytic effect.